(Electro)Sensing of Phenicol Antibiotics—A Review. Issue 14 (25th October 2016) - Pilehvar, Sanaz; Gielkens, Kristoffer; Trashin, Stanislav A.; Dardenne, Freddy; Blust, Ronny; De Wael, Karolien
Abstract : The presence of residues from frequent antibiotic use in animal feed can cause serious health risks by contaminating products meant for human consumption such as meat and milk. The present paper gives an overview of the electrochemical methods developed for the detection of phenicol antibiotic residues (chloramphenicol, thiamphenicol, and florfenicol) in different kinds of foodstuffs. Electrochemical sensors based on different biomolecules and nanomaterials are described. The detection limit of various developed methods with their advantages and disadvantages will be highlighted.